(untitled) (Research, Society and Development, 2022)
Education systems around the world have been impacted by a sudden disruption to classroom learning as the coronavirus pandemic forced the closure of all schools in March 2020 and the start of distance learning at home, forcing families, schools and students to work together in a more coordinated fashion. The main objective was to present critical information about the relationship between the family and the school in the face of the imposed scenario of distance learning caused by COVID-19. The relationships between the three groups involved must be improved to some extent to meet the needs that have arisen as a result of distance learning. In conclusion, the educational scenario during the pandemic has been one of the most significant challenges experienced in the recent history of education, even after the reduction of restriction measures and return to face-to-face classes around the world.